Analisis Putusan Mahkamah Agung Nomor 501 K/ PDT.SUS-PHI/ 2016 Tentang Pemutusan Hubungan Kerja - Sonhaji Sonhaji (Administrative Law and Governance Journal, 2018)
The purpose of this study is to know that the Certain Working Agreement on Oral Time is not allowed in the legislation, the Supreme Court judges consideration in deciding the case Number 501 K / Pdt.Sus-PHI / 2016 and the conformity of the decision with the law applicable in Indonesia. This study uses normative juridical method, which is analytical descriptive, with data collection method in the form of library study and supported by interview with judges. The results of the research show that First, the judge's decision is unfair to both parties litigation because the defendant is not punished to pay the wage of suspension (wage process) with emphasis on the consideration of unwritten PKWT so that by law become PKWTT. Second The process wage demands which are not accepted by the judge are contrary to the laws and regulations on employment and on the settlement of industrial relations disputes because the law requires that workers and employers continue to perform their obligations until the establishment of an Industrial Dispute Settlement Institution, including the obligation of employers to pay the wage of a suspension (wages process). So the Supreme Court Decision Number 501 K / Pdt.Sus-PHI / 2016 is less in accordance with the prevailing laws and regulations in Indonesia. Keywords: Oral Employment Agreement, Termination Dispute, Employment